2007
DOI: 10.1111/j.1365-3156.2006.01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs and coverage of reproductive health interventions in three rural refugee‐affected districts, Uganda

Abstract: Summarybackground Uganda has hosted an estimated 200 000 refugees in post-emergency phase settlements interspersed within host communities since 1990. However, refugee health service runs parallel to host in most refugee-affected districts. The process of integration of health services began in 1999.objective To estimate and compare the costs and coverage of reproductive health (RH) interventions in refugee and host populations in three rural West Nile refugee-affected districts of Uganda.methods Data on costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Several factors including inadequate resources -financial, human, physical infrastructure, low socio-economic status and the remote geographical location of the district, influence the health and social services delivery in the region. Previous studies by other researchers (13)(14) have also identified poor temporal and financial accessibility to health services for major obstetric interventions in the region. In the region (Arua district), both public and private means of transportation are scarce.…”
Section: Discussionmentioning
confidence: 87%
“…Several factors including inadequate resources -financial, human, physical infrastructure, low socio-economic status and the remote geographical location of the district, influence the health and social services delivery in the region. Previous studies by other researchers (13)(14) have also identified poor temporal and financial accessibility to health services for major obstetric interventions in the region. In the region (Arua district), both public and private means of transportation are scarce.…”
Section: Discussionmentioning
confidence: 87%
“…On the whole, the per capita cost of health care was 2.7 times higher for the refugee than the host population (US$13.12 vs. US$4.85), mainly because refugee health services are run by staff of higher professional qualifications and because drugs, materials and supplies are more readily available, prescribed and used in refugee (Orach et al. 2007).…”
Section: Experiences Influencing the Supply Sidementioning
confidence: 99%
“…Among three rural refugee-affected districts in Uganda, Orach et al (23) found that the per capita cost of health care and cost per reproductive health intervention was substantially higher for the refugees than the host population. Additionally, the proportion of refugees who attended ANC, gave birth in health facilities, and undertook major obstetric interventions were equally significantly greater compared to the host population.…”
Section: Refugees and Internally Displaced Persons Wellbeing Versus Hmentioning
confidence: 99%